Microsecond microwave generation in the diode and accompanying phenomena - Yuferov, V.B.; Kotenko, V.G.; Onishchenko, I.N.; Sorokovoy, L.G.; Kholod, Yu.V.; Skibenko, E.I. (Вопросы атомной науки и техники, 2000)
The processes of a gas desorption and ion production were investigated during generation of microwave pulses in a microsecond vircator. The influence of vacuum conditions was investigated and the velocity of cathode plasma was determined. Specific values of gas desorption and the partial composition was investigated for different cathodes. The parameters of the diode electron accelerator are the followings: beam energy 300 keV, beam current up to 10 kA, half-period 1,5 µs. Cathode and anode diameters are 10 cm and 20 cm, respectively. Vacuum chamber diameter is 50 cm, anode-cathode gap is 2 cm. The duration of microwave radiation is 0,5 µs, wavelength is about 10 cm, output microwave power is of about 1.5.10⁸ W. The amount of gassing reaches 0.3 n.cm3/pulse. Ion energy reaches 200-300 keV value.